Hormonal Shifts and Vision Changes: Addressing the Needs of Women During and After Pregnancy - Aliza Khan (International Journal of Women's Health Nursing And Practices, 2025)
Pregnancy and the postpartum period are marked by significant hormonal fluctuations that can profoundly affect a woman’s vision health. This review explores the relationship between hormonal shifts during pregnancy and the onset of common vision changes, including but not limited to dry eyes, blurred vision, and retinal changes. These changes are often temporary but can indicate underlying complications such as gestational diabetes, preeclampsia, and other pregnancy-related conditions that may threaten maternal and fetal well-being. The physiological mechanisms behind these visual disturbances, including changes in blood pressure, fluid retention, and hormonal influences on the eye, are examined in this article. Additionally, the review highlights the role of healthcare providers, particularly nurses, in identifying, monitoring, and addressing vision issues during pregnancy and the postpartum period. It emphasizes the importance of early detection and management strategies to mitigate risks for long-term visual impairments. Special attention is given to the management of common eye conditions, such as dry eye syndrome, refractive errors, and changes in intraocular pressure. The review also discusses postpartum vision changes, including potential complications like postpartum eclampsia and the exacerbation of preexisting visual conditions. By shedding light on the connection between hormonal fluctuations and vision health, this article underscores the critical need for specialized care, education, and support for women experiencing these changes. Nurses and healthcare providers play a vital role in ensuring the early identification of issues and providing timely interventions to prevent lasting harm. A proactive approach to maternal eye health is necessary to improve outcomes for women and ensure optimal health during this transformative life stage.
Keywords: Hormonal shifts; Pregnancy; nursing care; postpartum; vision changes